Presupozycje pytajne w dialogu medialnym na przykładzie programu »Otázky Václava Moravce« - Zura, Anna (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2014)
The aim of the publication is to examine the interrogative presuppositions in the Czech language in the conversational dialog on the basis of the Otázky Václava Moravce program. Presuppositional questions belong to the class of initiatory calques which imply a question through ascertainment, despite the absence of explicative factors. In the course of the undertaken analysis, it has been noted that the calques employed by the moderator of the program are chiefly inclusive and polemical, with the polemical calques frequently taking the form of attacking calques with the use of the direct address to the receiver and evaluative lexemes. It has also been revealed that the position of the moderator in the conversational dialog in media is dominant, which is validated by the linguistic means of expression.
Keywords: conversational dialog in media; Czech media; interrogative presuppositions; calques in dialog